Role of outer layer configuration on saline concentration sensitivity of optical fiber probe coated with ZnO/Ag nano-heterostructure. (April 2021) - Samavati, Zahra; Samavati, Alireza; Fauzi Ismail, Ahmad; Yahya, Noorhana; Rahman, Mukhlis A.; Hafiz Dzarfan Othman, Mohd
Highlights: Optical fiber sensor is modified via deposition of ZnO/Ag on partially unclad part. Structure and optical properties of the probe affected by ZnO configuration. Saline concentration sensitivity is a function of outer layer nanostructure shape. Vertically oriented ZnO nanorods shows superior saline concentration sensitivity. Abstract: Accurate monitoring of concentration changes in saline solution is prerequisite to control and minimize the negative effect of salt in water resources. A highly sensitive refractive index (RI) sensor is fabricated via coating a novel zinc oxide/silver (ZnO/Ag) bi-layer having different ZnO nanostructure shapes as an outer layer on partially unclad silica fiber. When the ZnO layer contact to different saline concentrations, its band-gap is altered and modifies the RI of the ZnO layer. The coupling of the evanescent light with surface plasmon resonance ( SPR) wave and absorption of evanescent light by the external medium are responsible for observing wavelength shift and intensity changes in the detected spectrum. For vertically oriented ZnO nanorods sample when IR light is used as a light source, by increasing the saline concentration from 0% to 20%, the wavelength is shifted from 1564.4 nm to 1573.3 nm and the intensity is dropped to 77% of its maximum value. The superior sensitivity obtained for vertically oriented ZnO sample is attributed to the larger surface area, higher average dispersion relation, better crystallinity, larger surface roughness and greater adhesion (interaction) with salt molecules compare to the other samples. The experimentally demonstrated highest intensity and wavelength sensitivity are 36 dB/RIU and 255 nm/RIU respectively.